Prophylactic Antibiotic Reduces the Risk of Peritonitis after Invasive Gynecologic Procedures. Issue 4 (July 2019) - Fan, Pei-Yi; Chan, Ming-Jen; Lin, Sheng-Hsuan; Wu, Hsin-Hsu; Chang, Ming-Yang; Tian, Ya-Chung; Kuo, George
Background: Peritonitis is a serious complication after invasive procedures in patients undergoing peritoneal dialysis (PD). Most studies that have investigated peritonitis following invasive gynecologic procedures enrolled small patient populations. This study focuses on the clinical presentation, outcomes, and effects of prophylactic antibiotic use before invasive techniques. Methods: A retrospective study was conducted on patients who underwent invasive gynecologic procedures between 2005 and 2015 in a tertiary medical center. Eligible patients were identified and enrolled and their demographic data were collected. The use of prophylactic antibiotics and the outcomes of peritonitis were recorded. Results: Twenty-six gynecologic procedures were performed on 18 PD patients. Seven episodes of peritonitis occurred in 6 patients after invasive gynecologic procedures. Eleven procedures were preceded by prophylactic antibiotic treatment (6 oral cefadroxil, 1 oral cefuroxime, 1 oral clindamycin, 1 intravenous [IV] ceftriaxone, 1 IV ceftazidime, and 1 IV cefazolin). The pathogens were diverse (group B Streptococcus, group D Streptococcus, E. coli, and Enterococcus ). All episodes of peritonitis were successfully treated using intraperitoneal antibiotics without recurrence, technique failure, or mortality. The odds ratio of peritonitis in the non-prophylaxis group was 20.29 (95% confidence interval 1.01 – 406.35, p = 0.0103). Conclusion: The use of prophylactic antibiotic treatment considerably reduced the risk of peritonitis after invasive gynecologic procedures.